2018
DOI: 10.1108/jec-08-2017-0064
|View full text |Cite
|
Sign up to set email alerts
|

It takes all kinds: understanding diverse entrepreneurial ecosystems

Abstract: Purpose This paper aims to explore the dynamics of entrepreneurial ecosystems with both rural and urban features, as well as the varied system requirements of differing types of entrepreneurs within such an ecosystem. Design/methodology/approach Using a mixed-methods case study approach, the study examined the Roanoke–Blacksburg region in western Virginia. Researchers conducted quantitative analysis of entrepreneurial metrics and network relationships, as well as qualitative analysis of data collected throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 19 publications
0
33
0
1
Order By: Relevance
“…For instance, Oberhauser, Pratt, and Turnage (2001) suggested that more rural economies, particularly those in Appalachia, rely on more informal kinship and community-based networks-networks not often tapped by more formal WD and TA organizations. Likewise, in a related study of entrepreneurial ecosystems, the authors of this study found that rural regions may thrive with the presence of a variety of interconnected and permeable informal networks where relationships can translate to tangible activities (Cowell, Lyon-Hill, & Tate, 2018). Another reason for SMMs' and service providers' inability to access or develop these networks is the economic upheaval that has occurred in many rural regions of the United States.…”
Section: Importance Of Utilizing and Developing Networkmentioning
confidence: 70%
“…For instance, Oberhauser, Pratt, and Turnage (2001) suggested that more rural economies, particularly those in Appalachia, rely on more informal kinship and community-based networks-networks not often tapped by more formal WD and TA organizations. Likewise, in a related study of entrepreneurial ecosystems, the authors of this study found that rural regions may thrive with the presence of a variety of interconnected and permeable informal networks where relationships can translate to tangible activities (Cowell, Lyon-Hill, & Tate, 2018). Another reason for SMMs' and service providers' inability to access or develop these networks is the economic upheaval that has occurred in many rural regions of the United States.…”
Section: Importance Of Utilizing and Developing Networkmentioning
confidence: 70%
“…Like comprehensive technology career pathway systems that connect workers to training for employment in local knowledge-intensive industries, entrepreneurial ecosystems emphasize the integration of multiple services to meet the specific needs of individual entrepreneurs (Cowell et al., 2018). These “ecosystems” represent coordinated efforts among a wide range of support organizations to provide business development advice, incubation and acceleration services, work space, mentorship, and start-up financing (Harrison and Glasmeier, 1997; Motoyama, 2020).…”
Section: Expanding Digital Opportunity: “Inclusive Innovation” and Institutional Capacity In The “Ordinary” Citymentioning
confidence: 99%
“…Ao passo que há dados suficientes para mapear o ambiente institucional, a carência de métricas sobre traços individuais de empreendedores, capazes de afetar a atividade empreendedora em nível local (Audrestch e Belitski, 2017), ainda persiste. Na tentativa de resolver esse problema e mensurar os relacionamentos entre organizações de apoio a empresas, empresas e indivíduos, Cowell et al (2018) utilizaram dados qualitativos, extraídos de entrevistas e grupos focais com empreendedores, bem como a análise de redes, mapeadas a partir de interações, identificadas em pesquisas sobre o uso de recursos dos empreendedores, e na base de dados do Twitter. Credit et al (2018), quando escreveram um artigo sobre o estado da arte das métricas de ecossistemas empreendedores, observaram que a maior parte dos estudos utiliza dados primários, devido a uma carência de dados secundários a respeito do empreendedorismo em geral.…”
Section: Ecossistemas De Empreendedorismounclassified